PENGARUH IKLIM ORGANISASI, PENDIDIKAN DAN PELATIHAN SERTA KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR PADA KANTOR PERWAKILAN BPKP PROVINSI SUMATERA SELATAN - Andri Kurnia Wira Sanjaya; Fakhry Zamzam; Neny Rostiati (Program Magister Manajemen Indo Global Mandiri University, 2021)
The purpose of this study was to determine the results of the analysis of the effect of Organizational Climate, Education and Training and Organizational Commitment either partially or simultaneously on Auditor Performance at the BPKP Representative Office of South Sumatra Province. This research used survey and verification methods with a quantitative approach, a population of 111 Auditors at the BPKP Representative Office of South Sumatra Province, 86 Auditors were taken as research samples using the Slovin formula, data collection using questionnaires, documentation and observation techniques. Data processing using SPSS version 25 analysis tools. The results of the research that Organizational climate partially has a positive and significant effect on the performance of auditors at the BPKP Representative Office of South Sumatra Province; Education and training partially have a positive and significant effect on auditor performance at the BPKP Representative Office of South Sumatra Province; Organizational Commitment partially has a positive and significant effect on auditor performance at the BPKP Representative Office of South Sumatra Province; Organizational Climate, Education and Training as well as Organizational Commitment simultaneously affect the increase in performance with the regression amount reaching 84,5% while the other 15,5% is influenced by variations of other variables.